Fly-In/Fly-Out, Flexibility and the Future: Does Becoming a Regional FIFO Source Community Present Opportunity or Burden? - McKenzie, F.; McKenzie, Fiona Haslam; Hoath, Aileen (Wiley-Blackwell Publishing Asia, 2014)
The resources boom in Australia has resulted in considerable competition for labour, particularly in remote mining areas. Shortage of skilled labour has led mining companies to source workers from far afield, while the high incomes created by a tight labour market draw labour from across the country through long-distance commuting arrangements such as fly-in/fly-out (FIFO). While much recent literature has focused on the impacts on receiving communities of these long-distance commuters, less attention has been given to the experience of source communities. This paper compares the situation between two regional towns in which long-distance commuters reside. The first, Busselton in Western Australia, is among several chosen by Rio Tinto to be labour source communities. The second, Stawell in Victoria, is looking to long-distance commuting as a response to the impending closure of their existing gold mine. Hence the case studies offer not only insights into source communities’ experience of longdistance commuting, but also a comparison between the bottom-up approach of Stawell in trying to establish FIFO with the experience of Busselton as an example of top-down labour sourcing. This paper seeks to highlight some of the development challenges encountered by communities and offer solutions as to how these might be addressed for the future.